2022
DOI: 10.1002/adfm.202210071
|View full text |Cite
|
Sign up to set email alerts
|

Over 24% Efficient Poly(vinylidene fluoride) (PVDF)‐Coordinated Perovskite Solar Cells with a Photovoltage up to 1.22 V

Abstract: Recently, organic–inorganic metal halide perovskite solar cells (PSCs) have achieved rapid improvement, however, the efficiencies are still behind the Shockley–Queisser theory mainly due to their high energy loss (ELOSS) in open‐circuit voltage (VOC). Due to the polycrystalline nature of the solution‐prepared perovskite films, defects at the grain boundaries as the non‐radiative recombination centers greatly affect the VOC and limit the device efficiency. Herein, poly(vinylidene fluoride) (PVDF) is introduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
46
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 55 publications
1
46
0
Order By: Relevance
“…This is consistent with the trend of V oc . 48 These results indicate that the synergistic action of the two additives reduces defects and improves the charge transfer kinetics. According to the equation In order to further study the charge recombination mechanism in PSCs, the variation of V oc with light intensity (P light ) was measured.…”
Section: ■ Results and Discussionmentioning
confidence: 90%
“…This is consistent with the trend of V oc . 48 These results indicate that the synergistic action of the two additives reduces defects and improves the charge transfer kinetics. According to the equation In order to further study the charge recombination mechanism in PSCs, the variation of V oc with light intensity (P light ) was measured.…”
Section: ■ Results and Discussionmentioning
confidence: 90%
“…38,39 Such composites have been shown to improve film crystallization kinetics 32,38 and help to passivate perovskite grains through polar interactions with the C−F groups. 35,37,38 In those studies, incorporation of fluoropolymers demonstrated promising results for perovskite function and stability and the fluoropolymer-perovskite interface was reasonably presumed to be inert; nonetheless, significant functionally relevant interfacial reactions are revealed in this work.…”
mentioning
confidence: 83%
“…Fluoropolymers (a different potential source of fluoride, as we show below) have previously been incorporated into perovskite devices as barrier materials in the form of encapsulants, transport layers, , and most notably as composites with the perovskite absorber layer. Several studies also indicate that even when incorporated as composites, a significant volume of the fluoropolymer is expelled from the composite layer to form a superficial interlayer. , Such composites have been shown to improve film crystallization kinetics , and help to passivate perovskite grains through polar interactions with the C–F groups. ,, In those studies, incorporation of fluoropolymers demonstrated promising results for perovskite function and stability and the fluoropolymer-perovskite interface was reasonably presumed to be inert; nonetheless, significant functionally relevant interfacial reactions are revealed in this work.…”
mentioning
confidence: 99%
“…[6][7][8][9] To date, 2,2 ′ ,7,7 ′ -tetrakis[N,N-di(4methoxylphenyl)amino]-9,9 ′ -spirobiuorene (spiro-OMeTAD) is widely adopted as a hole transporting material (HTM) in the state-of-the-art PSCs. [10][11][12][13] However, spiro-OMeTAD requires dopants (i.e., Li-TFSI and tBP) to improve the intrinsic low hole mobility. 14,15 These dopants could adversely affect the long-term stability of PSCs by facilitating the degradation of the perovskite material.…”
Section: Introductionmentioning
confidence: 99%
“…To date, 2,2′,7,7′-tetrakis[ N , N -di(4methoxylphenyl)amino]-9,9′-spirobifluorene (spiro-OMeTAD) is widely adopted as a hole transporting material (HTM) in the state-of-the-art PSCs. 10–13 However, spiro-OMeTAD requires dopants ( i.e. , Li-TFSI and tBP) to improve the intrinsic low hole mobility.…”
Section: Introductionmentioning
confidence: 99%